Effects of self-management program on glycemic control in patients with type 2 diabetes and glycosylated hemoglobin - Shafigheh Pourverdi; Farahnaz Mohammadi Shahboulaghi; Zahra Kashaninia; Pourya Rezasoltani (Journal of Holistic Nursing and Midwifery)
Abstract